2006
DOI: 10.1111/j.1600-0854.2006.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Long‐Range Transport Carriers Moving from the trans Golgi Network to Peripheral Endosomes

Abstract: The delivery of mannose 6-phosphate receptors carrying lysosomal hydrolases from the trans-Golgi network (TGN) to the endosomal system is mediated by selective incorporation of the receptor-hydrolase complexes into vesicular transport carriers (TCs) that are coated with clathrin and the adaptor proteins, GGA and AP-1. Previous electron microscopy (EM) and biochemical studies have shown that these TCs consist of spherical coated vesicles with a diameter of 60-100 nm. The use of fluorescent live cell imaging, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 28 publications
5
49
0
Order By: Relevance
“…AP1 is known to be located at the TGN and on tubulovesicular structures that also contain GGA1 and the mannose-6-phosphate receptor (Puertollano et al, 2001;Waguri et al, 2003). These structures are very dynamic, and they undergo transient fusions with peripheral endosomes that allows for the mixing of their contents, e.g., transferrin (Waguri et al, 2003;Polishchuk et al, 2006) and explains the partial colocalization of AP1 with transferrin (Figure 5; Waguri et al, 2003). Our triple-labeling experiments demonstrating colocalization of transferrin with AP1 and CVAK104 ( Figure 5) strongly suggest CVAK104 to be a component of the tubulovesicular structures and the peripheral endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…AP1 is known to be located at the TGN and on tubulovesicular structures that also contain GGA1 and the mannose-6-phosphate receptor (Puertollano et al, 2001;Waguri et al, 2003). These structures are very dynamic, and they undergo transient fusions with peripheral endosomes that allows for the mixing of their contents, e.g., transferrin (Waguri et al, 2003;Polishchuk et al, 2006) and explains the partial colocalization of AP1 with transferrin (Figure 5; Waguri et al, 2003). Our triple-labeling experiments demonstrating colocalization of transferrin with AP1 and CVAK104 ( Figure 5) strongly suggest CVAK104 to be a component of the tubulovesicular structures and the peripheral endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…3B). However, many clathrin-positive PGCs have a grape-like morphology (a tubule with several 'buds'), which suggests that entire chunks of TGN membranes that contain 2-3 clathrin-coated buds can be cleaved from the Golgi complex (Polishchuk et al, 2006). Fission along a budding PGC precursor might also be greatly facilitated by heterogeneous lipid microdomains (Roux et al, 2005).…”
Section: Fission Of Pgcs From the Tgnmentioning
confidence: 99%
“…The function of the TCs might be to mediate long-range distribution of mannose 6-phosphate receptors (MPR) and their cargo hydrolases to the peripheral cytoplasm (Puertollano et al, 2003). Similar to TCs in HeLa cells (Polishchuk et al, 2006), the tubules might not break down into CCVs en route to PVs in Giardia. In mammalian cells, it has been shown that TCs contain mannose-phosphate receptors, clathrin, Golgi-localizing Gamma-ear containing ARF-binding proteins (GGAs), and/or adaptor protein 1 (AP-1), and it was suggested that these might be uncoated during the TC-endosome fusion or could become integrated into the endosome membrane (Polishchuk et al, 2006).…”
Section: Clathrinmentioning
confidence: 99%
“…It is then possible that, as was observed in vitro (Zhang et al, 2007), clathrin may be organized in a hexagonal array, forming tubes instead of vesicles. Indeed, a different type of clathrin-coated transport carriers (TCs), consisting of larger tubular/vesicular structures having one or more clathrin-coated buds, have been identified (Polishchuk et al, 2006). These TCs travel long distances from the juxtanuclear area of the cell until they fuse with peripheral endosomes.…”
Section: Clathrinmentioning
confidence: 99%
See 1 more Smart Citation